The Behavior and Knowledge Contribution on Preventing Lack of Nutrition in Babies - Cristinawati B/R Haloho; Elisa Goretti Sinaga; Dewi Rinda Astuti; Fara Imelda Th Patty (PT Bukuloka Literasi Bangsa, 2025)
Based on WHO data in 2019, approximately 7.7% (52 million) of children under 5 years of age are malnourished. Indonesia is one of the countries in the world with a high rate of child malnutrition. In 2021, malnutrition among children reached 21.6%, while in East Kalimantan it reached 10.80% in children aged 0 to 23 months and 14.7% in children aged 0 to 59 months. There was a program from the health center to resolve this case, but in 2022, 92 children out of 742 children measured by weight per age (BB/U) were found to be malnourished. This study aims to analyze the relationship between knowledge and behavior as risks of malnutrition. This study was descriptive research using a cross-sectional design. This study was conducted in Manunggal Jaya Village, Kutai Kertanegara, East Kalimantan, involving 86 children (12-59 months) who were sorted by accidental sampling. The results of this study showed that 31 children out of 86 were malnourished. The bivariate analysis showed that there was a significant value with a p-value of 0.000 for behavior and knowledge in malnourished children. Low maternal behavior carries a 1.2 times risk of malnutrition in children, while low maternal knowledge carries a 5.2 times risk of malnutrition in children. The knowledge and behavior of mothers are very important in preventing malnutrition in children. Mothers who have good knowledge are not enough because knowledge does not work without action. Mothers who have good knowledge must apply that knowledge to make good food for their children. Keywords: Malnutrition, Knowledge, Behavior